Analisis Pinjaman Pada Pemerintah Daerah Kabupaten Manggarai - Rupertus Alfandi Jehalut; Aldarine Molidya; Cicilia A. Tungga (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to analyze the requirements, influencing factors, impacts, and effective solutions for loan management carried out by the Regional Government of Manggarai Regency in 2022. This regional loan analysis was carried out based on the provisions regulated in PP Number 56 of 2018 concerning “Regional Loans”. The research method used is descriptive qualitative. The type of research data used is qualitative and quantitative data with primary and secondary data sources. The data collection techniques in this research are interviews and documentation using the data analysis method proposed by Miles and Huberman. The results of this research show that regional loans made by the Manggarai Regency Government meet the requirements stated in PP Number 56 of 2018 Article 15, where the main factor in taking loans is to finance projects that are the development plans of the Manggarai Regency regional head. This regional loan has had a positive impact on infrastructure development and the DSCR value is 2.54 points, which means there is no indication of having a negative impact on the financial health of the Manggarai Regency Government area. The loan management solutions provided by research informants are in accordance with the principles of providing regional loans as stated in PP Number 56 of 2018 Article 3.